Compliment Strategies Across Gender of Indonesian Female Politicians: Netnography Approach - Duwila, Shanty A. Y. P. S; Astutik, Ari; Ardyanti, Erika (Indo-MathEdu Intellectuals Journal, 2025)
This article aims to shed light on the compliment strategies employed by men and women towards Indonesian female politicians, using a netnographic approach to uncover implications of these interactions. By exploring the intersection of gender, communication, and politics, this study contributes to the ongoing discourse on gender equality and empowerment in the political sphere. The study employs a qualitative descriptive method. Data consists of comments from netizens on the Instagram posts of five Indonesian female political figures. Documentation techniques are used for data collection, while Content Analysis is employed to data analysis. The steps include: selecting political posts, extracting top-liked compliments, identifying types of compliments, categorizing compliments, presenting data, interpreting the, and drawing conclusions. The results show that the compliment types that the women receive from men are in the forms of evaluations or appreciations. While women tend to give admiration and request. The patriarchal system in Indonesia does not serve as a barrier for Indonesian women to actively participate in politics. Men will appreciate and respect women who demonstrate competence and good traits